Application of Michael Reaction on 2-Phenyl-5-Oxazolone - Hamza, N.; Giath, Abdall; Ibrahim, M.N. (Asian Journal of Chemistry, 2010)
Michael reaction has been applied on 2-phenyl-5-oxazolone ring (1), which was used as Michael donor with arylmethylenecyanoacetic acid ethyl ester (2) as Michael acceptor. The Michael adducts had not been isolated but arylmetylene-2-phenyl-5-oxzolone (3) have been separated.